Work Motivation Reviewed From Job Satisfaction and Psychological Contracts in Employees - Atrizka, Diny; Tanoto, Steffi; Steven, Steven; Fransisca, Vanessa; Vania, Vania (Budapest International Research and Critics University, 2022)
This study aims to determine the relationship between job satisfaction and psychological contract to work motivation either partially or simultaneously. The research subjects used in this study were 91 employees and employees of PT XYZ. Sample selection using method stratified random sampling. Research data obtained from a scale to measure work motivation, job satisfaction and psychological contract. The calculation is done by performing classical assumption test which consists of normality test, autocorrelation test, multicollinearity test, heteroscedasticity test. Analysis of the data used is a multiple linear regression test through the help of SPSS 24 for windows. The results of data analysis showed that there was an influence between job satisfaction and psychological contract on work motivation with an F count of 51,588 and a significance value of 0.000 (p < 0.05). The results of the correlation analysis of the first minor hypothesis indicated that there was positive influence between job satisfaction and work motivation (Î² = 0.652, p = 0.000). The second minor hypothesis also showed that there was positive influence between the psychological contract on work motivation (Î² = 0.210, p = 0.006).